News and Perspective of Robotics - Perez Quispe, Victor (2001)
The present article sketches which are foregonely the future lines of the development of the robotics, in the world and in our environment, with two main objectives: to know the robots use in factory operations and services and to analyze the tendencies on the architecture of robots, the dynamic behavior, the sensorial integration and the programmiong.